Exploring the scattering directionality and light interaction in nanoparticle dimers of different semiconductors - Vergaz Benito, Ricardo; García-Cámara, Braulio; Algorri, José Francisco; Cuadrado, Alexander; Sánchez-Pena, José Manuel (Photonics Letters of Poland, 2017)
Assuming as a starting point our recent work on a dimer of silicon nanoparticles with light scattering directionality, we have explored the light interaction between the incoming and scattered electric fields in dimers made of other different semiconductors. The scattering directionality is achieved by accomplishing Kerker’s conditions. By directing the scattered light towards the gap of the dimer, interferential effects can be used to achieve high or low light intensities as a basis of all-optical nanoswitches. A comparison between dimers of different materials is shown. Full Text: PDF References R. Gómez-Medina, B. García-Cámara, I. Súarez-Lacalle, F. González, F. Moreno, M. Nieto-Vesperias and J.J. Sáenz, "Electric and magnetic dipolar response of germanium nanospheres: interference effects, scattering anisotropy, and optical forces", J. Nanophoton. 5 053512 (2011). CrossRef B. Rolly, B. Stout and N. Bonod, "Boosting the directivity of optical antennas with magnetic and electric dipolar resonant particles", Opt. Express 20 20376 (2012). CrossRef B. García-Cámara, R. Gómez-Medina, J.J. Sáenz, and B. Sepúlveda, "Sensing with magnetic dipolar resonances in semiconductor nanospheres", Opt. Express 21 23007-23020 (2013). CrossRef B. García-Cámara et al., "All-Optical Nanometric Switch Based on the Directional Scattering of Semiconductor Nanoparticles", J. Phys. Chem. C. 119, 19558?19564 (2015). CrossRef A.I. Barreda, H. Saleh, A. Litman, F. González, J-M. Geffrin, and F. Moreno, "Electromagnetic polarization-controlled perfect switching effect with high-refractive-index dimers and the beam-splitter configuration", Nat. Commun. 8, 13910 (2017). CrossRef R. Vergaz et al., "Control of the Light Interaction in a Semiconductor Nanoparticle Dimer Through Scattering Directionality", IEE Phot. Jour., 8(3), 4501410 (2016) CrossRef B. García-Cámara et al., "Size Dependence of the Directional Scattering Conditions on Semiconductor Nanoparticles", IEEE Photon. Technol. Lett. 27(19), 2059?2062 (2015). CrossRef